KEEFEKTIFAN MODEL GORDON DAN MOODY PADA PEMBELAJARAN MEMBACA PUISI SISWA SMP COBIG ISLAMIC SCHOOL MAKASSAR - Rosdiana, Rosdiana; Rapi, Muhammad; Djumingin, Sulastriningsih (Wahana Literasi: Journal of Language, Literature, and Linguistics, 2023)
This research aimed to; (1) Revealing the ability to read poetry by applying Gordon model; (2) Revealing the ability to read poetry by applying the Moody model; and (3) Revealing whether learning to read poetry through the applying of the Gordon model is more effective than the Moody model. This research used a quasi-experimental design. The instrument was an assessment rubric. The results were; (l) The ability of students to read poetry by applying the Gordon model is in the fairly skilled category with an average score of 62.50; (2) The ability of students to read poetry by applying the Moody model is in the fairly skilled category with an average score of 64.25; and (3) The data analysis showed that, values are obtained sig. (2 tailed) of 0.431 > 0.05 then H0 is accepted and HA is rejected. It can be concluded that the application of the Gordon model is not more effective than the Moody model. Thus, both models are equally effective in learning to read poetry at class VIII junior high school students of COBIG ISLAMIC SCHOOL Makassar.